Evaluation of selenium supply and status of inhabitants in three selected rural and urban regions of the Czech Republic - Kvícala, J; Zamrazil, V; Cerovská, J; Bednár, J; Janda, J (Biological trace element research, 1995)
Blood serum selenium of 65 men and hair selenium of 77 men from three regions of the Czech Republic (CR) were analyzed by neutron activation analysis, and 202 samples of urine from the same populations were analyzed for Se by the fluorimetric method to assess selenium status of these regions. Low status (53 micrograms Se/L of serum and 0.29 micrograms Se/g lyophilized hair as means) and very low urine selenium (8.7 micrograms/L urine) were detected. By these data, the CR is among the countries with the lowest Se intake. A comparison of studied regions is presented. Moreover, values of serum zinc were within the reference range, but mild to moderate deficiency in the supply of iodine was detected.
Keywords: venkovské obyvatelstvo; fluorescenční spektrometrie; Urban Population; mužské pohlaví; Freeze Drying; Male; Czech Republic; Humans; nutriční stav; Selenium; Spectrometry, Fluorescence; lidé; Middle Aged; lidé středního věku; selen; stopové prvky; neutronová aktivační analýza; Česká republika; senzitivita a specificita; Rural Population; městské obyvatelstvo; Neutron Activation Analysis; lyofilizace; Trace Elements; dospělí; Adult; Sensitivity and Specificity; Nutritional Status